Facilitating student behavioral engagement in ESP classroom through teachers’ scaffolding talk - Afendi Afendi; Ahmad Munir; Slamet setiawan (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2020)
This study aims to describe the language delivered by the teachers in the term of teachers’ scaffolding talk and the behavior engagement responded by the students in ESP agriculture Classroom. The investigation was conducted at a University in Sumbawa Besar, West Nusa Tenggara. Field note and video recordings were used to collect the data. During the observation, the data were then transcribed, simplified, displayed, and interpreted. The result shows there are four kinds of scaffolding talks namely prompting, dialoging, extension, and modeling from six kinds of scaffolding talk. Those scaffolding talks can facilitate the behavioral engagement of the students in ESP Classroom namely paying attention or focusing on the lesson, attempting to answer the question from the teacher, and exerting themselves actively participating in classroom interaction. These result suggest that lecturers and teachers may consider to apply the scaffolding talk before teaching the students in the classroom because methodology used by the teacher in teaching is as important as a talk in teaching. DOI: 10.26905/enjourme.v4i2.4264